Relation of Depression to Severity of Illness in Heart Failure (from Heart Failure And a Controlled Trial Investigating Outcomes of Exercise Training [HF-ACTION]) - Gottlieb, Stephen S.; Kop, Willem J.; Ellis, Stephen J.; Binkley, Philip; Howlett, Jonathan; O'Connor, Christopher; Blumenthal, James A.; Fletcher, Gerald; Swank, Ann M.; Cooper, Lawton (The American journal of cardiology, 2009)
Depression is common in patients with heart failure (HF), prognostic for adverse outcomes and purportedly related to disease severity. Psychological and physiologic factors relevant to HF were assessed in HF-ACTION, a large randomized study of aerobic exercise training in patients with systolic HF. The relation of objective and subjective parameters was compared with scores on the Beck Depression Inventory (BDI) to examine the hypothesis that depressive symptoms are better associated with perception of disease severity than with objective markers of HF severity. At baseline, 2,322 of 2,331 subjects entered into HF-ACTION completed questionnaires to assess depression (BDI) and quality of life (Kansas City Cardiomyopathy Questionnaire [KCCQ]). Objective markers of HF severity included ejection fraction, B-type natriuretic peptide, and peak oxygen consumption (using cardiopulmonary exercise testing, with evaluation of duration and respiratory exchange ratio also performed). Measures more likely to be affected by perceived functional status included New York Heart Association (NYHA) classification and the 6-minute walk test. Objective assessments of disease severity were slightly related (peak oxygen consumption) or not related (B-type natriuretic peptide and ejection fraction) to BDI scores. Using multivariate analysis (KCCQ not included), only age, gender, cardiopulmonary exercise testing duration, NYHA class, 6-minute walk distance, and peak respiratory exchange ratio independently correlated with BDI scores. In conclusion, depression was minimally related to objective assessments of severity of disease in patients with HF, but was associated with patient (and clinician) perceptions of disease severity. Addressing depression might improve symptoms in patients with HF.